Crystallinity integration of anatase (TiO2) nanocrystal by whole powder pattern fitting (WPPF) method: A Rietveld refinement study - Shanawaz Ahmed; Md. Khalid Hossain Shishir; Md. Tarikul Islam; Md. Ashikur Rahaman; Sahil Aman; Allah Rakha Aidid; Sumaiya Islam Sadia; Md. Masud Rana; Md. Ashraful Alam (Results in Materials)
High crystalline anatase synthesized by a unique simple route using titanium isopropoxide (TTIP) as precursor and isopropyl alcohol (IP) as peptizing agent. The Rietveld refinement analysis showed that the synthesized material is composed of 99.0 % anatase and 1.0 % brookite phases of titanium dioxide (TiO2). XRD characterized the prominent crystalline phase, providing insights into lattice parameters where a=b= 3.79068 Å, c= 9.50400 Å; α=β=γ= 90.0°; lattice strain 0.718, lattice volume 136.565 Å3, specific surface area 429.26 m2/g, dislocation density 0.0755 nm− 2, preference growth 0.119 and packing efficiency 70.09 %. The most intense diffraction was attributed to the (101) plane at 2θ = 25.39°. The average crystallite size through six identical models those were 3.64 nm (Scherrer equation), 6.47 nm (Williamson-Hall plot) confirming the formation of nano-crystalline anatase. Furthermore, the synthesized anatase exhibited a higher degree of crystallinity at 67.21 % compared to the ICDD standard of 65.06 %. This enhanced crystallinity and other crystallographic data, confirm the successful synthesis of the highly crystalline anatase with improved properties compared to the standard material. The Z-average size of 342.05 nm indicates the hydrodynamic diameter and 63.05 mV zeta potential depicted excellent stability of synthesized anatase in colloidal. The TEM images revealed the uniform crystal growth and average crystallite size ranges in size 8.712 nm. The SAED pattern computed the high crystalline anatase diffracted in individual crystal planes as well as HR-TEM revealed d-spacing 0.3501 nm corresponding to the (101) planes and TEM couple EDS confirmed 100.0 % unified anatase crystal. This research advances the understanding of the controlled synthesis of anatase nanoparticles and demonstrates the effectiveness of characterizing their crystalline structure.